The philosophical foundations of modern bioengineering - Ahmed Shogar, Ibrahim Adam; Abdul Rahman, Suzanah (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
This paper investigates the philosophical foundations of modern bioengineering to articulate its ethical framework. Engineering as an ultimate mechanism to transform knowledge into practice is essential for both physical and biological sciences. It reduces data, concepts, and designs to pictorial forms. The integration of engineering with the newly emerging biosciences, has presented a unique opportunity to overcome the major challenges that face the environmental and human health. To harness potentials of bioengineering and establish a sustainable foundation for green technology, modern scientists and engineers need to be acquainted with the normative questions of science. In addition to acquiring the general principles of scientific research and identifying the intrinsic goals of the endeavour, philosophy of bioengineering exposes bioengineers to both the descriptive ‘how’ questions of the physical world as well as the normative ‘why’ questions of values. Such an interdisciplinary approach is significant, not only for inspiring to acquire the genuine knowledge of the existing world, but also to expose the bioengineers to their ethical and social responsibilities. Besides introducing the conceptual framework of bioengineering, this paper has investigated the three major philosophies that have been dominating the theoretical presuppositions of scientific research method in history. Namely, (i) Systems biology approach; (ii) Evolutionary biology approach; and (iii) Mechanical view approach. To establish the ethical foundation of modern bioengineering, the paper, also conducted an analytical study on various branches of the emerging discipline of bioscience. The paper has concluded that adopting the interdisciplinary approach in research and education is essential to harness potentials of bioengineering and establish foundations of green technology. To achieve the final objectives of bioengineering, both the practical and theoretical knowledge of values must be acquired. The former is essential for invasion and innovation; meanwhile the later exposes bioengineers to the integrated discipline of knowledge and values.